Narratives of Appropriation: Abandoned Spaces, Entangled Stories and Profound Urban Transformations - Milián Bernal, Dalia (Writingplace, 2022)
Based on a narrative inquiry, this article presents the stories of four women who are, individually and collectively, appropriating vacant and abandoned urban spaces, physically transforming them, providing them with new uses, while unleashing other processes that have the potential to lead to profound systemic transformations. Building on these stories, the article discusses the notion of appropriation, utilizing Henri Lefebvre’s writings. The key argument of the article is that, through the appropriation of these urban spaces, these women are asserting their right to the city and their right to challenge and participate in the processes of urbanization.